A 2,3-butanedione protected chiral glycine equivalent - A new building block for the stereoselective synthesis of enantiopure N-protected α-amino acids - Dixon, D; Harding, C; Ley, S; Tilbrook, D (2003)
A new chiral glycine equivalent 7 has been synthesised from glycidol using a chiral memory protocol, and its use in the synthesis of N-Z protected α-amino acids was demonstrated in a series of diasteroselective lithium enolate alkylation reactions and subsequent acid hydrolyses.